The Impact Of Training Program To Cooperatives Entrepreneur And Small Business Performance In Riau Province - Hamid, Liswar; ', Haryetti (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2012)
This research is aimed to 1) determine the effect of training program on entrepreneurship development and small business in Riau Province, 2) determine the dominant factors in the development of the entrepreneurial spirit. By using sampling technique and descriptive analysis, the participants who attended the training program which was held by department of cooperative is 35 people. Even though there was a mixed response from this research, it received a total of as much as 74,3% response from the respondents and that indicated the training program which has done was very useful and able to foster an entrepreneurial spirit of the participants. To foster the entrepreneurship, there are still constraints in capital and business facilities were needed. The dominant material relationships affect entrepreneurship are creativity, innovation, hard work, and expectation.